If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(6 + -5x) = 1 (6 * glo + -5x * glo) = 1 (6glo + -5glox) = 1 Solving 6glo + -5glox = 1 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -1 + 6glo + -5glox = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 6glo + -5glox = 0 The solution to this equation could not be determined.
| 19-n=3 | | 8n-3(n-7)=0 | | 8lnx=9 | | 2500=60+36x | | 8x^2-24x+32=0 | | y+7/3=1+3y-2/5 | | 7.9x-3.5=28.1 | | 27^1/3= | | (x+2y-1)dx-(2x+y-5)dy=0 | | 12/11=x/12 | | 2x-13-6x-2/5=1/3 | | -4=5-8(-4) | | (8-3x)(5x-x)=(3x-4)(x-6)-13 | | f(-4)=5-8x | | M-6=17 | | 3500=100+39x | | 100+39=3500 | | 2(4-g)-3(2g-6)=8(3g-1)-11(g-5) | | 4x+5y=2470 | | Y=cot(7x) | | 14+5n=14+3n | | x^2y+y^2x=14040 | | 2u+9=45 | | c=(a-u)/n | | ac=mc+n | | 12w^2+9w^3=0 | | 16-h^2+6hy+9y^2= | | x=(y-q)/m | | x=315/80 | | 315/80 | | X^3-3x-4x+12=0 | | -4+5+m=-3+7 |